Circular economy in the building and construction sector: A scientific evolution analysis. (December 2021) - Norouzi, Masoud; Chàfer, Marta; Cabeza, Luisa F.; Jiménez, Laureano; Boer, Dieter
Abstract: The building industry is responsible for considerable environmental impacts due to its consumption of resources and energy, and the production of wastes. Circular Economy (CE), a new paradigm can significantly improve the sustainability of this sector. This paper performs a quantitative scientific evolution analysis of the application of CE in the building sector to detect new trends and highlight the evolvement of this research topic. Around 7000 documents published 2005 to 2020 at Web of Science and Scopus were collected and analyzed. The bibliometric indicators, network citation, and multivariate statistical analysis were obtained using Bibliometrix R-package and VOSviewer. The co-occurrence analysis showed five keyword-clusters, in which the three main ones are: (i) energy and energy efficiency in buildings; (ii) recycling, waste management and alternative construction materials; (iii) sustainable development. The analysis showed that researchers pay close attention to "sustainability", "energy efficiency", "life cycle assessment", "renewable energy", and "recycling" in the past five years. This paper highlights that (i) the development and use of alternative construction materials; (ii) the development of circular business models; (iii) smart cities, Industry 4.0 and their relations with CE, are the current research hotspots that may be considered as potential future research topics. Graphical abstract: Image 1 Highlights: A comprehensive, quantitative analysis of the literature of the CE in buildings. The documents were collected from WoS and Scopus (2005–2020). Data from publications, authors, affiliations and key concepts were analyzed. Evolution, hotspots, leading entities & collaborations in the topic were discussed. The topic analyzed is in an emerging stage and will continue to grow in the future.